ESL teachers’ belief system and its impact on technology-based english language teaching in Pakistan - Wajahat, Taj Abbasi (2024)
Teachers' Belief System (TBS) and its impact on technology-based teaching of English is of great significance for Second Language Teaching in Pakistan. Technology-based teaching basically plays an important role in the development of English as economic and educational corridors for the progress of the country. Limited utilization of technology for English language teaching is an alarming situation which needs to be pointed out and handled properly. The research brings forth different beliefs concerning the issue as dependent and independent variables under belief system which impact technology-based English language teaching in the country. The thesis also reflects on the relationship between Teachers’ Belief System and its other relevant factors (Dependent Constructs) in using technological applications for teaching of English as Second Language in Pakistan. Moreover, the present research discusses the effects of cross-culturalism in relation to Teachers’ Belief System on the use of technology by English as Second Language teachers in their teaching practices. The study is also very important as there is little research to be found on the topic across the country. The topic also focusses on an area which is highly remote in the utilization of educational technology. Knowledge about cross-culturalism in relation to teachers’ beliefs is an addition to the existing research. Nevertheless, the study uses Decomposed Theory of Planned Behaviour (DTPB) which is a combination of other two theories: Theory of Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). A mixed method research design based on survey questionnaire, semi-structured interviews together with classrooms’ observations was used to collect data of the study from lecturers and professors teaching in Hazara University (HU) and Abbottabad University of Technology (AUST), Khyber Pukhtunkhwa (KPK), Pakistan. Quantitative data was collected from one hundred and fifty two (152) respondents whereas twelve (12) participants took part in semi structured interviews. Moreover, observations of two classes of Bachelor of Science (BS) in English were made as a part of qualitative data collection. Quantitative and Qualitative data were analyzed through SPSS-22 and N-Vivo software. Sampling adequacy for quantitative tool is ensured through Kaiser- Meyer-Olkin and Bartlett tests. Pro-max with Kaiser Normalization and Regression Analysis tests are also used in the study to find out the relationship between teachers’ belief and its relevant factors. Results of the present study point out limited use of technology in English language teaching despite the efforts made by the government of Pakistan. Teachers’ belief and its relevant factors such as limited resources, lack of professional development, subjective norms and limited utilization of cross-culturalism in language teaching are found out to be mutually related in influencing the incorporation of technology in English language teaching in Pakistan. Similarities and differences between the results of the quantitative and qualitative data are also revealed as per the findings of the study. The results of the research highlight limited technological knowledge of English as Second Language teachers to be an obstruction in the successful utilization of technology in their teaching. Moreover, beliefs and attitudes of English as Second Language teachers also affect their use of technology as per the findings of the study. In addition, the use of cross-culturalism also helps English as Second Language teachers to enhance their incorporation of technology in their teaching practices according to the quantitative and qualitative results of the study. Subjective norm acts as a barrier to the utilization of technology on the part of language teachers according to the findings of the research. Nevertheless, the results of the research favor the establishment of different courses and sessions in relation to the teachers’ professional development for the utilization of technology in English as Second Language teaching in Pakistan. Both the qualitative and the quantitative results of the research also emphasize the provision of technological tools and technical staff by stake holders for its successful integration by English as Second Language teachers concerning technological resources. Furthermore, the research suggests inclusion of different cultures in textbooks for collaborative and task-based acquisition of English as Second Language in the present teaching contexts which may also lead to independent learning environments. Flexible treatments by institutional authorities for the utilization of available technology on the part of the English as Second Language teachers in teaching English in Pakistan are also recommended by the present study.